Use of Lithotripsy in a Calcified Saphenous Vein Graft - van Gameren, Menno (JACC Case Rep, 2020)
Percutaneous coronary interventions in saphenous vein grafts can pose a variety of challenges, such as severely calcified lesions. If these lesions are nondilatable, lithotripsy can arguably be a proper tool for lesion preparation. We present a case in which a nondilatable, calcified saphenous vein graft was successfully treated using Shockwave lithotripsy. (Level of Difficulty: Intermediate.)